150k views
0 votes
2. 2x + y = -4
5x + 3y = -6

1 Answer

3 votes

Answer:

x=15/4,y=-8.25

Explanation:

Well to begin with it make both y's equal so multiply the first equation by 3 making it into: 6.6x+3y=-12. next subtract this new equation by the other one making it one equation as, 1.6x=-6, simplify to get: x=15/4, or 3.75 input that into one of the equations the secound one would be easier to make it 18.75+3y=-6 simplify again, 3y=-24.75 than you get y as y=-8.25

User Bibangamba
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.